The Role of Customary Law in the Development of National Law in the Modern Era - Purnomo, Vicki Dwi; Supeno , Bambang Joyo; Lisdiyono , Edy (PT FORMOSA CENDEKIA GLOBAL, 2024)
Customary law plays an important role in the development of national law in Indonesia, especially in the modern era marked by globalization and modernization. Customary law serves as a reflection of the rich and diverse local cultural values, and plays a role in various aspects of community life, including the resolution of rescue, management of natural resources, and protection of the rights of indigenous peoples. In the era of decentralization and regional autonomy, customary law is increasingly recognized in local policies and becomes an important instrument in maintaining the unique legal identity of each region. Formal recognition of customary law is also reflected in various national regulations, such as the Law on Villages and the Basic Agrarian Law, which accommodate customary law in facing the challenges of modernization and globalization, customary law must adapt to the modern era